Daylight photodynamic therapy with 1.5% 3‐butenyl 5‐aminolevulinate gel as a convenient, effective and safe therapy in acne treatment: A double‐blind randomized controlled trial. Issue 5 (12th December 2015) - Kwon, Hyuck Hoon; Moon, Ki Rang; Park, Seon Yong; Yoon, Ji Young; Suh, Dae Hun; Lee, Jee Bum
Abstract: While daylight photodynamic therapy (PDT) is a simpler and more tolerable treatment procedure for both clinicians and patients, it has never been applied for acne treatment. In this study, we evaluated efficacy, safety and histological changes of facial acne after application of the novel variant of 5‐aminolevulinate (ALA)‐ester, 1.5% 3‐butenyl ALA‐bu gel, using daylight only as the potential visible light source. Forty‐six acne patients were randomly assigned to either ALA‐bu or vehicle application group in a double‐blind fashion. Both groups applied the allocated gel to facial acne lesions every other day for 12 weeks. At the final 12 week, both inflammatory and non‐inflammatory acne lesions had decreased significantly by 58.0% and 34.1% in the ALA‐bu group, respectively. Only a few patients expressed mild adverse effects. In the histopathological analysis, attenuated inflammatory cell infiltrations were observed and immunostaining intensities for interleukin‐8, interleukin‐1β, matrix metalloproteinase‐9 and phosphorylated nuclear factor‐κB were reduced concomitantly. Changes of their mRNA expression demonstrated comparable patterns. In conclusion, this ambulatory PDT was effective, very well tolerated and convenient for treating inflammatory acne lesions. Experimental results correlated well with clinical results. This novel regimen would provide a viable option for acne therapy.